Classification and location of faults in transmission line via wavelet transform - Nurul Idayu Yusoff, 1993- , author; Jasrul Jamani Jamian, supervisor; Fakulti Kejuruteraan Elektrik (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2016